Redes de interação entre aves frugívoras e plantas: padrões de interação e influência de atributos - Silva, Adriano Marcos da (2017)
Seed dispersal is an essential ecosystems process, which has different implications for plant and animal diversity. Among the seed dispersal animals, birds are the most important vectors in several ecosystems. This thesis had three network-level goals: (1) which way to analyze the bird's diversity most influence in the interaction network structure; (2) measuring the complementarity and redundancy in the interaction networks and (3) determining whether the presence of congeneric plants species that are morphologically and nutritionally similar, lead to the formation of interaction modules in the network. At species level, the goals were to determine (1) which morphological and behavioral traits influence in fruit selection and interactions intensity; (2) which extinction proneness traits most influence on the importance of each species to the structure of the interaction network and (3) which traits determine the contribution of each species to the modular structure of the network. The database were composed by interaction networks between frugivorous birds and plants that was collected from literature or own data and the bird's traits consisted of measurements taken from individuals captured in mist-nets or museum and literature. Linear models and network analysis were used as statistical. In relation to the goal (1), functional diversity is the diversity parameter that best explained the variance in network structure of the network, gape width was the trait that best explained the fruit selection and the combination of frugivory level and body mass best explained the intensity of interactions. The goal (2), networks analyzed showed high specialization and low redundancy and the combination of level frugivory and forest dependence better explained the importance of each species in the network structure. The goal (3), using weighted networks, modules were detected in all interaction networks, but none of the birds traits were related to his role within the modular structure. This study demonstrates that the trait set of a bird species is crucial to its role within the frugivory interaction network and that knowing these traits is an important step to define conservation and management. We also highlight the importance of diversity of functional traits in the structuring of interaction networks, especially in communities with low functional redundancy.